Pengaruh Kualitas Pelayanan Dan Kualitas Produk Terhadap Kepuasan Pelanggan Sambal Galak Grand Wisata Di Bekasi - Karina Rachmawati; Dovina Navanti; Franciscus Dwikotjo Sri Sumantyo (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The purpose of the study is to ascertain how customer satisfaction at Sambal Galak Grand Wisata in Bekasi is impacted by the quality of the products and services offered. This kind of study is descriptive and quantitative. This type of primary data is generated by an online questionnaire. The population is the grand tour community in Bekasi with a sample of 140 respondents with the hair formula. In this technique, data analysis using SPSS 26. The validity, reliability, normalcy, multiple linear regression, hypothesis, F, and determination coefficient tests were among the data analysis methods employed in this investigation. The study's findings partially explain how customer happiness is influenced by service quality. Partially the effect of Product Quality has an influence on Customer Satisfaction. Simultaneously, The criteria that affect customer satisfaction are Service Quality and Product Quality.